Phylloicus mirabilis (Trichoptera: Calamoceratidae), a new species from Rio de Janeiro state, southeastern Brazil - Cavalcante, Bruna Maria Silva; Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2018)
Phylloicus Müller 1880 is an endemic Neotropical genus of Calamoceratidae characterized by adults that have diurnal to crepuscular habits. Currently, the genus contains 57 species, with 23 of these species recorded from Brazil. Herein, a new species of Phylloicus is described and illustrated based on specimens collected in Malaise traps from Southeast Region, Brazil. The new species can be characterized by the unusual lateral membranous lobes of abdominal segments IV–VII, metathoracic tibiae with brushes of setae and distal emargination, and the wide and long coremata on abdominal pleura VII. Otherwise, the genital structure is similar to that of Phylloicus monneorum Dumas & Nessimian 2010, being distinguished by the subtrapezoidal tergum X, the globose harpago of the inferior appendages, and the moustache-shaped phallotremal sclerite.